Classic and aids-related Kaposi's sarcoma an ultrastructural investigation - Celleno, L... (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 1993)
Electron microscopy was used to study lesional bopsy specimens from 25 patients with Kaposi's sarcoma (20 with the classical form and 5 associated with AIDS). The study relevealed that the AIDS-associated lesions were characterized by more rapidly developing damage to the capillary endothelium with respect to the classical lesions; tubuloreticular structures were also found more often within the cells of the former lesions. Our ultrastructural findings suggest that the endothelial cells of the affected blood vessels may be responsible for the histogenesis of the disease. in this study we were not able to demonstrate the presence of viral particles within the cells of the classical lesions. Virus-like particles were observed within the AIDS-associated lesions, but there was no sign of viral replication.
Keywords: Acquired immunodeficiency syndrome; Biopsy, needle; Complications; Diagnosis; Endothelium, vascular; Sarcoma, kaposi's; Ultrastructure